Changing incidence of esophageal cancer among white women: analysis of SEER data (1992–2010) - Raman, Rachna; Deorah, Sundeep; McDowell, Bradley D.; Hejleh, Taher Abu; Lynch, Charles F.; Gupta, Amit (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : To analyse trends in the incidence rates of adenocarcinoma and squamous cell carcinoma of the oesophagus (ACE and SCC, respectively) in white women between 1992 and 2010. Material and methods : We used data from the Surveillance, Epidemiology, and End Results (SEER program to identify cases of esophageal cancer). Age adjusted incidence rates (IR) were calculated for ACE and SCC for two different time periods (1992–1996 and 2006–2010) and stratified by age, stage, and histologic type. We used joinpoint analysis to detect changes in rates between 1992 and 2010. Results: Between the time periods 1992–1996 and 2006–2010, the age-adjusted incidence rates for SCC in white women decreased from 1.2/100,000 to 0.8/100,000 personyears, and for ACE it increased from 0.5/100,000 to 0.7/100,000 personyears. Similar to white men, the increase in the incidence of ACE was consistent for all stages and all age groups in white women. However, it was most pronounced in women aged 45–59 years, where the incidence of ACE (0.9/100,000 person-years) in 2006–2010 exceeded the incidence of SCC (0.6/100,000 person-years). On joinpoint regression analysis, an inflection point was seen in 1999 for ACE, indicating a slower rate of increase for ACE after 1999 (annual percentage change of 8.00 before 1999 vs. 0.88 starting in 1999). Conclusions : The incidence of ACE is increasing in white women, irrespective of age or stage. Indeed, ACE is now more common than SCC in white women between 45 and 59 years of age.